Thomas Gray in Copenhagen - Davis, Philip J. author. aut Link
XV, 192 p. 63 illus., 51 illus. in color.
Keywords: The further adventures of a feline philosopher and friend. Could it be? Hans Christian Andersen - who wrote so lovingly of inchworms and ugly ducklings - an unrepentant despiser of cats? That's the rumor that the philosophical feline, Thomas Gray, and her (yes, her) cohort, Cambridge don Lucas Fysst, are determined to snuff out. In Copenhagen to attend a philosophers' convention, they go on the hunt for a missing Andersen manuscript that will set the record straight. A sequel to the popular Thomas Gray, Philosopher Cat, Philip J. Davis' latest is a whimsically written and illustrated tale - part history, part parody, and all fun.